A Disintegrin and Metalloprotease‐22 Attenuates Hypertrophic Remodeling in Mice Through Inhibition of the Protein Kinase B Signaling Pathway. Issue 2 (22nd January 2018) - Ren, Lingyun; Wu, Chuangyan; Yang, Kai; Chen, Shanshan; Ye, Ping; Wu, Jie; Zhang, Anchen; Huang, Xiaofan; Wang, Ke; Deng, Peng; Ding, Xiangchao; Chen, Manhua; et al.
Abstract : Background: Severe cardiac hypertrophy can lead to cardiac remodeling and even heart failure in the end, which is a leading cause of cardiovascular disease–related mortality worldwide. A disintegrin and metalloprotease‐22 (ADAM22), a member of the transmembrane and secreted metalloendopeptidase family, participates in many biological processes, including those in the cardiovascular system. However, there is no explicit information on whether ADAM22 can regulate the process of cardiac hypertrophy; the effects that ADAM22 exerts in cardiac hypertrophy remain elusive. Methods and Results: We observed significantly increased ADAM22 expression in failing hearts from patients with dilated cardiomyopathy and hypertrophic cardiomyopathy; the same trend was observed in mice induced by transaortic constriction and in neonatal rat cardiomyocytes treated by angiotensin II. Therefore, we constructed both cardiac‐specific ADAM22 overexpression and knockout mice. At 4 weeks after transaortic constriction, cardiac‐specific ADAM22 knockout, by the CRISPR/Cas9 (clustered regularly interspaced palindromic repeat (CRISPR)–Cas9) system, deteriorated the severity of cardiac hypertrophy in mice, whereas cardiac‐specific ADAM22 overexpression mitigated the degrees of cardiac hypertrophy in mice. Similarly, altered ADAM22 expression modulated the angiotensin II–mediated cardiomyocyte hypertrophy in neonatal rat cardiomyocytes. After screening several signaling pathways, we found ADAM22 played a role in inhibition of protein kinase B (AKT) activation. Under the cardiac‐specific ADAM22 knockout background, AKT activation was enhanced in transaortic constriction–induced mice and angiotensin II–stimulated neonatal rat cardiomyocytes, with a severe degree of cardiac hypertrophy. Treatment of a specific AKT inhibitor attenuated the transaortic constriction–enhanced AKT activation and cardiac hypertrophy in mice. Conclusions: The findings demonstrated that ADAM22 negatively regulates the AKT activation and the process of cardiac hypertrophy and may provide new insights into the pathobiological features of cardiac hypertrophy.